Exploring the therapeutic potential of Quercus ilex acorn extract in papillomavirus-induced lesions - Ana I. Faustino-Rocha; Maria João Pires; Maria João Neuparth; Helena Vala; Cármen Vasconcelos-Nóbrega; Irene Gouvinhas; Ana Novo Barros; Maria Inês Dias; Lillian Barros; Margarida M. S. M. Bastos; Lio Gonçalves; Luís Félix; et al. (Veterinary World)
Background and Aim: Papillomaviruses (PVs) infections have been documented in numerous animal species across different regions worldwide. They often exert significant impacts on animal health and livestock production. Scientists have studied natural products for over half a century due to their diverse chemical composition, acknowledging their value in fighting cancer. Acorns (Quercus ilex) are believed to have several unexplored pharmacological properties. This study aimed to evaluate the in vivo safety and cancer chemopreventive activity of an infusion extract of Q. ilex in a transgenic mouse model of human PV (HPV)-16, which developed squamous cell carcinomas through a multistep process driven by HPV16 oncogenes.